Strain transfer analysis of fiber Bragg grating sensor assembled composite structures subjected to thermal loading. (1st April 2019) - Wang, Huaping; Dai, Jian-Guo
Abstract: Optical fiber sensing technology has been widely used for thermal strain detection of civil structures subjected to the environmental temperature variations. Due to the fragile material nature, bare optical fibers are seldom used in practice, as they cannot resist the harsh service environment. A packaging measure is usually required to enhance the durability of optical fiber-based sensors for reliable long-term detection. However, the existence of packaging and bonding materials brings about strain transfer loss, which makes the optical fiber readings not accurately represent the actual strains of the host material. This paper presents a combined experimental and theoretical study on a four-layer optical fiber sensing composites (i.e., the host material, an adhesive bonding layer, the sensing fiber, and its protection layer) subjected to thermal loading to correct the above-mentioned strain transfer error. Aluminum and polypropylene (PP) plates with different thermal expansion coefficients were surface-bonded with fiber Bragg grating (FBG) sensors and then exposed to various temperatures (30–70 °C). Theoretical study was developed to investigate how the strain measurement error was influenced by the thermal deformation incompatibility of multiple contacted layers (i.e., the optical fiber, the protective layer, the adhesive layer and the hosting material) with different thermal expansion coefficients. The accuracy and effectiveness of the proposed strain transfer function was then validated through comparisons with the test results. Based on the theoretical analysis, the sensitivity of the relevant material and geometrical parameters on the strain transfer efficiency was discussed to instruct the design of FBG based sensors. The proposed error-modification formula can be used to effectively improve the strain measurement accuracy and instruct the optimum design of FBG based sensors applied to civil structures under thermal loading.